2014
DOI: 10.1155/2014/543090
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Potential for Evaluation of Concrete Flaws Using Nondestructive Testing Methods

Abstract: Adoption of periodic or continuous monitoring strategies to assess condition state of infrastructure elements is a vital part of service life management (SLM). NDT methods are increasingly seen as an attractive and viable strategy to support condition monitoring. Over the last 15 years, the LEME research group at UFRGS has investigated several aspects related to the use of the ultrasonic pulse velocity (UPV) method and its potential for real field applications. One of the main advances involved the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Exactly for this potentiality, the UPV has been the most investigated NDT in research in Structural Tests and Materials Laboratory of the Federal University of Rio Grande do Sul (LEME/UFRGS). In various research work conducted, on the field and in the laboratory, a technique of UPV was developed, mapping with indirect readings, and confirmed that the method, when properly employed, can offer ease of implementation, fast and suitable fault detection capability [3,4,5,6,7,8,9]. Several researches related to UPV and concrete.…”
Section: Introductionmentioning
confidence: 94%
“…Exactly for this potentiality, the UPV has been the most investigated NDT in research in Structural Tests and Materials Laboratory of the Federal University of Rio Grande do Sul (LEME/UFRGS). In various research work conducted, on the field and in the laboratory, a technique of UPV was developed, mapping with indirect readings, and confirmed that the method, when properly employed, can offer ease of implementation, fast and suitable fault detection capability [3,4,5,6,7,8,9]. Several researches related to UPV and concrete.…”
Section: Introductionmentioning
confidence: 94%
“…The results of the rebound hammer enable to obtain the imperfections on the surface of the concrete (Lorenzi et al, 2014). He added that the result of rebound hammed reflects to hardness of the surface and less potential to detect the internal defects.…”
Section: Rebound Hammer Testmentioning
confidence: 99%
“…Common defects in concrete structures include corrosion, cracking and spalling, deterioration, de-bonding, surface and subsurface deformations, delamination, and material performance impairment [ 56 , 57 , 58 , 62 ]. The classification scheme proposed by Rehman et al [ 63 ] (see Figure 5 ) suggests that ultrasonic sensors and IR thermography for structural health monitoring are suitable techniques for assessing various types of defects, including spalling, corrosion, cracking, and delamination. In contrast, acoustic emissions are only appropriate for delamination, cracking and spalling, and deterioration.…”
Section: Sensors For Health Monitoring Of Agricultural Structuresmentioning
confidence: 99%